Pengembangan Internal Locus of Control dalam Pelayanan Konseling dan Implikasinya terhadap Perbedaan Budaya Klien - Marjohan Marjohan (Jurnal Konseling dan Pendidikan, 2013)
The goal of counseling, among other thing,   is to develop an internal locus of control of a clients. Research, especially in western cultures, has shown that those with an internal locus of control were correlated to their characters, they are:  hard work, problem solving skilss, optimistic, engaging in social activities and high in achievement motivation. However, for clients who are not from western cultures a tendency to foster an internal locus of control in the counseling process should be considered properly. This paper describes how to  enhance client’s internal locus of control for those who do not embrace western cultures